The effect of the context of the case in directing the significance between the speaker and the interlocutor in grammatical analysis in the Sabban footnote - Yahya, Malik; Safit, Wahid; Aljafan, Eabdaleziz ’Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study deals with the impact of the context of the situation in the direction of the speaker and the speaker in the grammatical analysis in the Sabban footnote, an attempt to show its concept and importance. The context of the case is a major means or hypothesis created by the language to gain benefit in many sections of grammar. It has the same role in the analysis of language through its association with the data that surrounds the language, besides that the significance is the basic purpose of the process of speech, and the research divided into three sections namely: the intent of the speaker, the benefit of the addressee, and the effect of the circumstances and conditions surrounding the text in grammatical analysis, As a grandmother of evidence represented by Sabban in a footnote, and some grammarians in Issues differences, trying to extend its views as possible. تتناول هذه الدّراسة أثر قرينة الإسناد في التّحليل النّحوي عند الصّبان في حاشيته على شرح الأشموني محاولة تبين مفهومه وأهميته؛ إذ تعدّ قرينة الإسناد إحدى أبرز القرائن المعنوية، وهي قرينة تخلقها اللغة لتحقيق التماسك في الكلام ويُلجأ إليها في التحليل النحوي، موضحة أثر قرينة الإسناد في مجال الدلالة، كما أنّ لها الدور الأهم في التّحليل النّحوي من خلال ارتباطها بالعلاقات التركيبيّة التي تربط الجمل حتى تتحقق الاستقامة ويصل المتلقي إلى الإفادة، وقد قُسِّم البحث إلى ثلاثة أقسام هي: مفهوم الإسناد في اللغة والاصطلاح، الإسناد في تركيب الجملة الاسميّة بين ركنيها، والإسناد في تركيب الجملة الفعليّة في باب الفاعل والنائب عنه، وجاءت الدارسة وفقاً لما وجدته من شواهد تمثّله في حاشية الصبان، وما لبعض النحاة في مسائله من آراء حول الإسناد، محاولاً بسط الآراء ما أمكن.